3D printing of circular materials: Comparative environmental analysis of materials and construction techniques - Shoukat Alim Khan (14778226) (2023)
The use of 3D printing in construction activities can help to reduce waste, lower energy consumption, and minimize the environmental impact of building projects. As technology continues to advance, it has the potential to play a major role in the development of cleaner, more sustainable production processes in the construction industry. For each such innovation, it is essential to ensure its environmental sustainability at an early stage of development. This study aims to assess the potential environmental advantages and disadvantages of newly developed construction and demolition waste (CDW)-based geopolymer materials for 3D printing of built-environment structures. The study identifies potential "hot spots" of the developed process where environmental impact is highest and develops strategies to reduce or mitigate negative impacts. Life Cycle Assessment (LCA) was carried out for three cases of CDW-based 3D printed structures, Portland cement-based 3D printed structures, and conventional masonry construction methods and materials, to analyze the environmental impact of CDW-based 3D-printed designs and their comparative analysis. The results showed that geopolymer-based 3D printed construction resulted in the lowest global warming potential of 488 [kg CO2 eq] as compared to 595.6 [kg CO2 eq] for ordinary Portland cement-based structure and 533.7 [kg CO2 eq] for conventional masonry construction of the equivalent structure. The main environmental "hot spot" identified for the geopolymer-based 3D printed construction process was the amount of electrical energy required for the mechanical processing of waste materials, which was more than 61% of the total GWP impact. In addition to decreasing solid CDW, the developed approach has significant potential for improvement by using more sustainable energy sources and reducing the amount of solid CDW generated. Other Information Published in: Case Studies in Construction Materials License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.cscm.2023.e02059